Microbial profiling of polychlorinated biphenyl contaminated soil for bioaugmentation strategy / Kimberly Ng Hui Ling - Kimberly Ng , Hui Ling (2024)
Polychlorinated biphenyls (PCBs) are one of the persistent organic pollutants (POPs) which contaminate the soils, in turn causing adverse effects on the biota and environment. One of the promising methods for remediation of these contaminated soils is bioaugmentation. Thus, a proper assessment of the microbial community of contaminated sites is needed before the bioaugmentation method can be applied to minimise possible antagonistic effects. This study aimed to evaluate the chemical properties of the PCB-contaminated soil and uncontaminated soil, followed by profiling the bacterial community of the PCB-contaminated soil using 16S metagenomic sequencing and compared it with the bacterial profile of an uncontaminated soil using DNA barcoding. The PCB degrading bacteria was also isolated, identified and tested for their ability to degrade PCB by the PCB degradation assay using shake flask. Results showed that the contaminated soil was acidic (pH 4.45) and has low soil nutrient content, in particular N and P content, compared to the uncontaminated soil which was close to neutral (pH 6.34) and higher soil nutrient content. The contaminated soil contains several major phyla like Proteobacteria, Acidobacteriota and Actinobacteriota and minor phyla such as Verrucomicrociota, Bacteroidota and Firmicutes. When comparing with the uncontaminated soil, there are differences in the abundance and composition of bacterial phyla and classes in contaminated soil as compared to that of uncontaminated soil. Gammaproteobacteria class was abundant in the contaminated soil while the Alphaproteobacteria class has a greater abundance in the uncontaminated soil. The presence of PCB/hydrocarbon degraders such as Pseudomonas spp., Bacillus spp., Rhodococcus spp. and Ralstonia spp. were recorded from the contaminated soil. The PCB degrading strain isolated was Bacillus spp. In conclusion, the bacterial community in the contaminated soil differed from that of uncontaminated soil and Bacillus spp. was the only PCB-degrading strain isolated from this study.